PEMANFAATAN APLIKASI ELSA SPEAK DALAM MENINGKATKAN KEMAMPUAN SPEAKING SECARA AKTIF DI PONDOK PESANTREN BAITUL QUR’AN KREMBUNG-SIDOARJO - Purnomo, Ryan; Haromainy, Muhammad Muharrom Al; Wardono, Mohammad Setyo (Universitas Mataram, 2025)
The most difficult part of English for students is pronunciation. Pronunciation is considered one of the keys to successful speaking. Because of its importance, students often struggle to master it. Therefore, the purpose of this community service activity was to provide an interactive and enjoyable pronunciation learning method using the ELSA Speak application. This community service activity was conducted at the Baitul Qur'an Islamic Boarding School in Krembung, Sidoarjo. Participants were students and teachers from the same Islamic boarding school. This training activity aimed to improve speaking skills through the use of the application. The authors used pre- and post-tests to assess the effectiveness of the ELSA Speak application. Data were collected through tests, questionnaires, and interviews to evaluate students' abilities and perceptions. The results showed that the ELSA Speak application was effective in improving pronunciation, as indicated by higher scores on the application assessment after the post-test compared to the pre-test. Furthermore, questionnaire responses strongly indicated that students considered the ELSA Speak application an effective method for learning pronunciation. This application can help students improve their pronunciation skills compared to before.